Vertical velocity observations of a FIRE II cirrus event - Song, Ran, author; Cox, Stephen K., author (Colorado State University. Libraries, 1994)
The development of doppler radar wind profilers and their subsequent deployment have dramatically improved the spatial and temporal resolutions of wind observations. While the horizontal winds deduced from these observations are generally reliable, serious questions remain on the ability to reliably observe the vertical wind component. In an upper tropospheric cirrus cloud environment often characterized by weak backscatter signal strength, small magnitude vertical motions, high altitude and short life cycle, this problem is especially difficult. A review of the echo generating mechanisms for a 400 MHz radar system is presented. This study further examines the feasibility of determining reliable vertical motion fields from both individual and a network of wind profiler observations. Data employed in this research were collected during the FIRE II experiment in November and December of 1991. Vertical motions were calculated in three ways: directly from the doppler radial velocity observations, from a quasi-V AD method utilizing the four non-zenith profiler beams, and by applying the kinematic method to profiler network data. The deduced vertical wind fields from each method are compared. This research also includes a diagnostic study of a jet streak system observed on 26 November 1991; this study emphasizes the thermal and dynamic instability structures, the vertical forcing the ageostrophic circulation. Results from the diagnostic and previous theoretical studies are compared with the vertical velocity fields deduced from wind profiler observations.
July 1994.
Keywords: Cirrus clouds; Vertical wind shear